2022
DOI: 10.3389/fnins.2022.988283
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral edema after ischemic stroke: Pathophysiology and underlying mechanisms

Abstract: Ischemic stroke is associated with increasing morbidity and has become the main cause of death and disability worldwide. Cerebral edema is a serious complication arising from ischemic stroke. It causes an increase in intracranial pressure, rapid deterioration of neurological symptoms, and formation of cerebral hernia, and is an important risk factor for adverse outcomes after stroke. To date, the detailed mechanism of cerebral edema after stroke remains unclear. This limits advances in prevention and treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 153 publications
0
24
0
1
Order By: Relevance
“…Their median age was 71 [IQR 62-79] years and 45% were females. Baseline NIHSS was median 14 [8][9][10][11][12][13][14][15][16][17][18]. Time from last-seen-well to arrival was median 170 [73-347] minutes.…”
Section: Resultsmentioning
confidence: 99%
“…Their median age was 71 [IQR 62-79] years and 45% were females. Baseline NIHSS was median 14 [8][9][10][11][12][13][14][15][16][17][18]. Time from last-seen-well to arrival was median 170 [73-347] minutes.…”
Section: Resultsmentioning
confidence: 99%
“…These pathophysiological processes in ict severe damage upon neurons, glia, and endothelial cells, leading to irreversible neuronal injury [1,22]. The severity of IS correlates with factors such as the size of cerebral infarction, cerebral edema, and hemorrhagic transformation, all of which are linked to unfavorable outcomes in AIS [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…In certain situation, this effect can excessively increase the BBB permeability, allowing different molecules to permeate and subsequently undergo metabolic transformations in the brain tissue, with the formation of pathological deposits that can initiate degenerative processes and neuronal death. Simultaneously, ionic, osmotic and vasogenic cerebral edema can occur, which can also have a detrimental effect on the structure and function of the CNS [ 36 ]. nNOS may play a major role in BBB disruption [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the burst of both eNOS and nNOS, following acute cerebral ischemia, mediates the increase in NO production. The consequence is the occurrence of vasogenic cerebral edema with brain tissue damage [ 36 ]. The production of NO occurs in two waves, the first of which is characterized by the transient increase in NO synthesis, and the second one by an increased synthesis of NO that lasts up to 4–7 days.…”
Section: Introductionmentioning
confidence: 99%